Study of the Bioconversion Process of Black Soldier Fly (Hermetia Illucens) Larvae in Decomposition of Various Variations of Organic Waste - Wildan Muhlison; Listya Purnamasari; Irwanto Sucipto; Tri Wahyu Saputra; Nanda Khoirun Nisa Ahmad (TECHNO: JURNAL PENELITIAN, 2021)
Poor waste management will affect various aspects such as environmental pollution due to piles of garbage that disturb the community. It needs a waste treatment process and one of them is the bioconversion process. This process uses the biological agent Black Soldier Fly (Hermetia illucens). This research was conducted with three organic matter variations, namely tofu pulp, eggplant pulp, and pumpkin pulp as bioconversion media. The ability of BSF larvae in bioconversion organic waste can be seen from several parameters, namely temperature, media pH, larvae weight growth, WRI (Waste Reduction Index), survival rate, consumption substrate and feed residue. The results were analyzed by one-way ANOVA test then the Least Significant Difference (LSD) test with a significance level of 95%. The research results with different bioconversion media are significantly different results on the ability of BSF larvae in the decomposition process. Tofu pulp media show the best results compared to other media with suitable conditions for the decomposition process with a final temperature of 28.8 oC, pH 7, weight growth 28.35%, WRI 5.38%, and 80.71% substrate consumption.